MEMBUAT GAMBAR DALAM PERSFEKTIP HUKUM ISLAM (Studi Perbandingan antara Yusuf Qarᾱḍawi dan Muhammad Ali Al-Ṣabuni) - Tarmizi Tarmizi; Jamhuri Jamhuri (Universitas Islam Negeri Ar-Raniry, 2019)
Islamic studies terms, images are called ṣurah, and making pictures is called taṣwir. The scholars differed about the law of images, whether it was creating them or owning them. Yusuf Qarᾱḍawi argues that what is haram is taṣwir which has a physical form and a shadow. As for taṣwir that is painted on paper, walls and so on, where the taṣwir has no shadow and is physical, it is permissible. Meanwhile, according to Muhammad Ali al-Ṣabuni taṣwir that is forbidden is that which is hand-painted which is an imitation of animate beings and also taṣwir that has a physical form and has a shadow, namely a statue. According to Yusuf Qarᾱḍawi, the permissibility and prohibition of the image depends on the object being drawn and whether or not there are illat prohibitions contained in the hadith in the image. Al-Qarᾱḍawi also said that a photo is permissible if the object is halal, and it is not an image that is included in the hadith of the Prophet. Meanwhile, Muhammad Ali al-Ṣabuni forbids images of animate beings that are intact but allows images of inanimate beings and inanimate creatures. Al-Ṣabuni also categorizes photographic images into images that are prohibited in the Prophet's hadith, this is based on the generality of the Prophet's hadith regarding images and the punishment for the image maker. Thus, basically the traditions about taṣwir have legal illat, but besides that there are other things that need to be considered in making pictures and photographs. If the image or photo violates the law, it must be prohibited to make it.